P431Flecainide or propafenone oral bolus to facilitate electrical cardioversion of persistent atrial fibrillation. (18th June 2020) - Compagnucci, P; Barbarossa, A; Centanni, M; Urbinati, A; Ciliberti, G; Stronati, G; Dello Russo, A; Guerra, F; Capucci, A
Abstract: Background: electrical cardioversion (ECV) of atrial fibrillation (AF) is a pivotal component of the rhythm control approach. Although ECV is safe and effective in the majority of patients, approximately one patient out of ten experiences an early or very early recurrence. In order to improve ECV's success rate, oral or intravenous amiodarone pre-treatment is commonly prescribed and followed by a second ECV attempt. However, due to the long time needed to achieve therapeutic levels and the high risk of phlebitis, faster and safer strategies to facilitate ECV are highly needed. Purpose: to evaluate whether the administration of a flecainide or propafenone oral bolus followed by ECV would prove effective and safe in facilitating conversion to sinus rhythm in patients with persistent AF and a prior ECV failure. Methods: we conducted a prospective, open-label, single center observational study. The case group was formed by patients with persistent AF and a prior ECV failure receiving flecainide or propafenone oral bolus (at the same doses used for the "pill-in-the-pocket" approach) followed by a second ECV attempt 3 hours after drug ingestion. For comparison, we selected patients with a prior ECV failure that underwent amiodarone-facilitated ECV. Before ECV, amiodarone was either administered orally for at least 1 month or intravenously for 24 hours. The primary outcome was conversion to sinus rhythm, defined as sinus rhythm persisting for at least 12 hours after ECV. Results: patient's characteristics were well balanced in the 3 groups, apart from slightly lower left ventricular ejection fraction values in the amiodarone groups. The day after ECV failure, 29 patients received oral flecainide at a 200 mg (n = 15) or at a 300 mg (n = 14) dose and one patient received oral propafenone at a 600 mg dose before undergoing a second ECV attempt. In nine patients, amiodarone was given intravenously for 24 hours. Amiodarone was prescribed orally to 22 patients for a median of seven weeks at an average daily dose of 241.4 mg. In the flecainide/propafenone group, one patient converted to sinus rhythm one hour after drug ingestion; among the other 29 subjects, the second ECV was effective in 23 (cumulative effectiveness: 80.0%). In the intravenous amiodarone group, 2 patients converted to sinus rhythm during drug infusion; among the other 7, the second ECV proved effective in 4 (cumulative effectiveness: 66.7%). In the oral amiodarone group, ECV was successful in 17 patients (77.3%). When comparing the three groups, the primary outcome occurred in a similar proportion of patients (Chi-squared test: p = 0.34; Fisher's exact test: p = 0.24). Serious adverse events were not reported. Conclusions: flecainide or propafenone oral bolus quickly facilitated conversion to sinus rhythm in the vast majority of patients with persistent AF and a prior ECV failure with a low inherent risk of adverse events. Flecainide effectiveness proved similar to intravenous or oral amiodarone.